Investing in low-carbon transitions: energy finance as an adaptive market. (3rd April 2017) - Hall, Stephen; Foxon, Timothy J; Bolton, Ronan
Abstract : The amount of capital required to transition energy systems to low-carbon futures is very large, yet analysis of energy systems change has been curiously quiet on the role of capital markets in financing energy transitions. This is surprising given the huge role finance and investment must play in facilitating transformative change. We argue this has been due to a lack of suitable theory to supplant neoclassical notions of capital markets and innovation finance. This research draws on the notion from Planetary economics: Energy, climate change and the three domains of sustainable development, by Grubb and colleagues, that planetary economics is defined by three 'domains', which describe behavioural, neoclassical, and evolutionary aspects of energy and climate policy analysis. We identify first- and second-domain theories of finance that are well established, but argue that third-domain approaches, relating to evolutionary systems change, have lacked a compatible theory of capital markets. Based on an analysis of electricity market reform and renewable energy finance in the UK, the 'adaptive market hypothesis' is presented as a suitable framework with which to analyse energy systems finance. Armed with an understanding of financial markets as adaptive, scholars and policy makers can ask new questions about the role of capital markets in energy systems transitions. Policy relevance This article explores the role of financial markets in capitalising low-carbon energy systems and long-term change. The authors demonstrate that much energy and climate policy assumes financial markets are efficient, meaning they will reliably capitalise low-carbon transitions if a rational return is created by subsidy regimes or other market mechanisms. The authors show that the market for renewable energy finance does not conform to the efficient markets hypothesis, and is more in line with an 'adaptive' markets understanding. Climate and energy policy makers that design policy, strategy, and regulation on the assumption of efficient financial markets will not pay attention to structural and behavioural constraints on investment; they risk falling short of the investment levels needed for long-term systems change. In short, by thinking of financial markets as adaptive, the range of policy responses to enable low-carbon investment can be much broader.